(untitled) (Comillas Journal of International Relations, 2019)
The purpose of this article is to analyze the evolution of the Spanish international cooperation and development policy until 2010. Such policy identifies poverty as the global problem which Spain tries to solve in an international context. However, it is also a resource for the Country´s foreign policy. This public policy is developed taking into account some basic facts, such as the Transition to Democracy period (1977-1982), the recent new Constitution (1978), the integration into the European Communities (1986), the incorporation into the Regional Development Banks, as well as a more active participation in the EU Fundings and in the Programmes of Development and Humanitarian Aid of the United Nations system.